2022
DOI: 10.1021/acs.nanolett.1c04512
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the Thermal Properties of Superconducting Magic-Angle Twisted Bilayer Graphene

Abstract: The allegedly unconventional superconducting phase of magic-angle twisted bilayer graphene (MATBG) has been predicted to possess extraordinary thermal properties, as it is formed from a highly diluted electron ensemble with a record-low carrier density (n) of ∼10 11 cm −2 and electronic heat capacity (C e ) of <100k B . While these attributes position MATBG as a groundbreaking material platform for revolutionary calorimetric applications, these properties have so far not been experimentally shown.Here, we reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 57 publications
0
12
0
1
Order By: Relevance
“…[16,40] Finally, the ultrafast Umklapp-assisted electron-phonon cooling, enhanced density of states, and rich phase diagram are appealing for single-photon detection in the highly sought after mid-IR wavelength range. [44,45]…”
Section: Origin Of Enhanced Coolingmentioning
confidence: 99%
“…[16,40] Finally, the ultrafast Umklapp-assisted electron-phonon cooling, enhanced density of states, and rich phase diagram are appealing for single-photon detection in the highly sought after mid-IR wavelength range. [44,45]…”
Section: Origin Of Enhanced Coolingmentioning
confidence: 99%
“…The experiments on magic-angle (θ = 1.05 • ) twisted bilayer graphene (MATBLG) [4][5][6] have established the existence of a variety of interesting phases , including correlated insulating phases [29][30][31][32][33][34][35][36][37][38][39] and superconductivity [40][41][42][43][44]. Their discovery has been followed by considerable theoretical efforts aimed at understanding their origin.…”
Section: Introduction-mentioning
confidence: 99%
“…12−15 Except for the way of adjusting thermal conductivity, such as porosity design, 16,17 doping, 18 grain refinement, 19,20 and defects, 21,22 weak van der Waals (vdW) connections between layers make interlayer twist a reliable approach for regulating the thermal conductivity of layered 2D materials. 23−27 Di Battista et al 28 demonstrated that the magic-angle twisted bilayer graphene can obtain the coexistence of ultralow electronic heat capacity, thermal conductance, and carrier density. Cheng et al 29 discovered that different stacking modes of twisted graphene produce phonon scattering sites that lower the thermal conductivity.…”
Section: ■ Introductionmentioning
confidence: 99%
“…As a novel category of layered materials, 2D transition-metal dichalcogenides (TMDCs), which can be expressed as MX 2 (M = Mo, W, Ti, and X = S, Se, Te), have been proven to be ideal candidates for advanced thermoelectric materials due to their relatively high electrical conductivity, low thermal conductivity, high Seebeck coefficient, and wide tunability of the inherent thermoelectric parameters. Except for the way of adjusting thermal conductivity, such as porosity design, , doping, grain refinement, , and defects, , weak van der Waals (vdW) connections between layers make interlayer twist a reliable approach for regulating the thermal conductivity of layered 2D materials. Di Battista et al demonstrated that the magic-angle twisted bilayer graphene can obtain the coexistence of ultralow electronic heat capacity, thermal conductance, and carrier density. Cheng et al discovered that different stacking modes of twisted graphene produce phonon scattering sites that lower the thermal conductivity.…”
Section: Introductionmentioning
confidence: 99%